Chemodynamics of the Milky Way and disc formation history: Insight from the RAVE and Gaia‐ESO surveys. Issue 8 (30th September 2016) - Kordopatis, G.; Wyse, R. F. G.; Binney, J.
Abstract: Multi‐object spectrographs have opened a new window on the analyses of the chemo‐dynamical properties of old Milky Way stars. These analyses allow us to trace back the internal mechanisms and the external factors that have influenced the evolution of our Galaxy, and therefore understand fundamental aspects of galaxy evolution in general. Here, we present recent results from the RAdial Velocity Experiment (RAVE) and the Gaia‐ESO survey. These surveys explore the Milky Way properties in different ways, in terms of sample size and selection, magnitude range, and spectral resolution. We focus here on (i) the first direct detection of evidence for radial migration within the thin disc, providing insight into the history of spiral structure of the Milky Way, and (ii) the chemo‐dynamical characterisation of the metal‐weak thick and thin discs, for which chemo‐dynamical models still have difficulties in reproducing.